Synthesis of Quinolines via Iron-Catalyzed Redox Condensation of Alcohols with 2-Nitrobenzyl Methyl Ether/2-Nitrobenzyl Alcohols - Wang, Qi; Wang, Meirong; Li, Hui-Jing; Zhu, Shuai; Liu, Ying; Wu, Yan-Chao (Synthesis, 2016)
An iron-catalyzed redox condensation of 2-nitrobenzyl alcohols, formic acid, and alcohols has been developed, which affords substituted quinolines with carbon dioxide and water as the only side products. With the use of formic acid as a redox moderator to fill the electron gap of the global redox condensation process, the reaction goes smoothly with a smaller amount of alcohol in comparison to previous reports (i.e. 1.2 equiv versus 3.3–4 equiv). The reaction goes equally well when 2-nitrobenzyl methyl ether was used instead of 2-nitrobenzyl alcohol under otherwise identical conditions, shedding a new light on the study of this quinoline synthetic method.
Keywords: quinolines; 2-nitrobenzyl alcohols; iron catalysis; redox condensation; Friedländer annulation